Encouraging Learners to Become Better-informed Consumers of L2 Learning Opportunities - White C; Bown J (EUROKD Egitm Danismanlik Group, 2020)
The notion of language learners as informed consumers developed by Cohen and White (2008) takes up the issue of how best to develop the knowledge, skills and awareness of language learners given the infinite variety of language learning opportunities. The informed consumer approach focused not only on developing awareness of both formal and informal learning environments, but also on enhancing the ability to critically appraise those opportunities and to optimise language learning within them. In this article we trace how the notion of language learners as informed consumers has been drawn on in innovative studies of technology-mediated language learning; a common focus of those studies has been on ways of fostering awareness of the potential of particular technology-mediated learning environments and the relevant knowledge and skills which would support the active and effective use of those environments. We show how strands of the informed consumer approach have been used to investigate expertise and affordances in electronic dictionary use (Levy & Steel, 2015) and the trajectories of distance learners of Chinese (Tasker, 2010). In the latter part of the article we consider the experiences and reflections of learners of Arabic in a study abroad context in Jordan as part of Project Perseverance; findings from that project open up new dimensions of what it means to be an informed consumer of language instruction in relation to specific situational and cultural norms and constraints. To conclude the article identifies not only the distinctive contribution of the informed consumer approach but also how it sheds light on the ways in which individuals seek out and curate personally meaningful sites for language learning within their life worlds.
Keywords: language consumer awareness; informed choice; technology-mediated language learning; study abroad